If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(8w-4)+6w=-2(w+5)
We move all terms to the left:
-2(8w-4)+6w-(-2(w+5))=0
We add all the numbers together, and all the variables
6w-2(8w-4)-(-2(w+5))=0
We multiply parentheses
6w-16w-(-2(w+5))+8=0
We calculate terms in parentheses: -(-2(w+5)), so:We add all the numbers together, and all the variables
-2(w+5)
We multiply parentheses
-2w-10
Back to the equation:
-(-2w-10)
-10w-(-2w-10)+8=0
We get rid of parentheses
-10w+2w+10+8=0
We add all the numbers together, and all the variables
-8w+18=0
We move all terms containing w to the left, all other terms to the right
-8w=-18
w=-18/-8
w=2+1/4
| 5(3x-1)=8x+10 | | X√2+2x-3=0 | | 2y-1+2(3y+2)=-4(y+3) | | -4x+2=3x+16 | | -2=y/4 | | 7(x-2)=6x+1-3(-3x-1) | | 3y+84=60 | | (x-12)=132 | | -4(-5x+4)-3x=2(x-1)-5 | | 4(u+4)=-3(4u-4)+8u | | (0.20)(10)=0.05(10)+0.40(10–x | | 1+12=n | | 51+34=x | | 6n+8=108 | | (0.20)(10)=0.05(10)+0.40(10–x) | | 59=29^x | | 8x+5(12*4)=25 | | 4X-5+5z=33 | | 6x+2=18-2x | | 10x7=93 | | 5(2f-4)=10 | | 6(z+3)−9=−27 | | a+6=8-(9+a) | | Z-6z=5z-4-2 | | a+6=8-(9=a) | | R^2=-7+8r | | 4×2+16x+36=0 | | X+x/2+6=180 | | 1-2x+3=x-8 | | (5−6m)/(m^2−16)=0 | | 2x-10+x30+20=180 | | 35y+5=21y+15 |